ETIOPATHOGENETIC AND CLINICAL CHARACTERISTICS OF DIFFUSE TOXIC GOITER - Babadjanova Sh.A.; Qurbanova G.Ch.; Filiz Erdogan M. (Journals Park Publishing, 2023)
The article provides detailed information about the effects of diffuse toxic goiter on human life and body, their treatment with several different methods, laboratory diagnostics and assessment of hormonal changes.
Keywords: diffuse toxic goiter, anemia, thyroid gland, autoimmune, thyrotoxicosis, non-thyroid disease, exophthalmos.